The enemy in Psalm 22 : a cognitive interpretation in an African context - Kotze, Zac (Journal for Semitics, 2010)
The enemy as animal in Psalm 22 is commonly interpreted against the background of depictions of demons with animal features in the iconography of the ancient Near East. However, since the adversary is also presented in human terms, most contemporary interpretations suggest that the antagonist is a projection of the psalmist experiencing an intense form of anxiety. This article explores the possibility that the animal spirits were believed to be manifestations of the witch as enemy in the worldview of ancient Israel.
paid